Etika Komunikasi Keluarga Perspektif Al-Qur’an: Kajian Tafsir Tematik dan Implementasinya dalam Kehidupan Rumah Tangga di Kota Tanjungbalai - Aprilia Putri; Ernawati Beru Ginting (Kartika: Jurnal Studi Keislaman, 2026)
Family communication plays an important role in shaping character and creating a harmonious household. However, digital technology and social change have shifted family communication ethics, as reflected in the decline of direct interaction, the use of impolite language, and increasingly emotional communication patterns. Meanwhile, the Qur’an provides ethical guidance through the principles of qaulan sadīdan, qaulan karīman, qaulan layyinan, and qaulan ma‘rūfan. This study aims to analyze the concept of family communication ethics from the Qur’anic perspective, its implementation in the household life of the Tanjungbalai community, and the obstacles faced by Muslim families in applying it. This research uses a qualitative approach with field research. Data were collected through interviews, observation, and documentation, then analyzed using thematic interpretation and an interactive analysis model. The findings show that Qur’anic communication ethics are implemented through Malay cultural practices, including family address terms, the traditions of upah-upah, manyonggot, and bakombur. The obstacles include generational gaps in understanding, ego, limited interaction time, digital media disruption, economic pressure, and the declining role of extended families. This study implies the need to strengthen Qur’anic communication contextually within modern Muslim families.